Genetic aspects of dental caries - Cogulu, Dilsah; Saglam, Ceren (Frontiers in Dental Medicine, 2022)
Dental caries is a common chronic disease affecting humans in all age groups. Various factors can affect the formation of caries including demineralization and remineralization processes with oral flora; dietary and oral hygiene habits; salivary composition, flow rate, pH and buffering capacity; morphological features of the teeth; fluoride exposure; and environmental and socioeconomic factors. One of the most important factors causing inter-individual variations in caries susceptibility is the host genetics. Several genes affect individual caries susceptibility. Genes play a role in immune response, development of saliva and tooth enamel. The present review aims to overview the literature focusing on the genetic features of dental caries.